Early recovery of basic mobility under femoral nerve block after hip fracture surgery – A propensity score matched pilot study. Issue 11 (November 2021) - Ogawa, Takahisa; Seki, Keiko; Tachibana, Tetsuya; Hayashi, Hiroto; Moross, Janelle; Kristensen, Morten Tange; Shirasawa, Shinichi
Highlights: Early recovery in 3-day CAS and 1-day CAS on postoperative day 2 were significantly associated in patients who underwent FNB. Beneficial association between FNB and recovery time was observed especially in femoral neck fracture patients without dementia. We utilized CAS to evaluate patient's short-term mobility of function, including those with dementia. Abstract: Background: : Previous studies have shown better pain reduction utilizing femoral nerve block (FNB) in patients who underwent hip fracture surgery. However, few studies have focused on the recovery of physical function after FNB, and most studies excluded patients with dementia. We investigated the association between FNB performed in the operating room and the recovery of physical function after hip fracture surgery, including patients with dementia. Methods: A total of 103 patients with a mean age of 87.4 years who underwent hip fracture surgery under spinal anesthesia between July 2015 and December 2017 (46 patients receiving a single injection of FNB and 57 standard care) were enrolled. Patients with FNB versus standard care were matched by a propensity score to adjust for patient characteristics. An anesthesiologist performed FNB with 20ml of 0.2% ropivacaine, and the standard care group received intravenous 1000 mg acetaminophen or 50mg flurbiprofen once after surgery. After matching, 78 patients were analyzed. Our primary outcome was 3-day cumulated ambulation score (CAS, 0-18 points) and secondary outcomes were 1-day CAS on postoperative day 1-3 and length of hospital stay. We also stratified patient groups based on the presence of dementia and fracture type. Results: Patients undergoing FNB had significantly better 3-day CAS compared to standard care (mean [SD], 8.72 [3.42] vs 7.33 [2.62]; mean difference, 1.38 [95%CI; 0.03 - 2.74]; p = 0.048) and 1-day CAS on postoperative day two (mean [SD], 3.10 [1.39] vs 2.56 [0.94]; mean difference, 0.54 [0.01 - 1.07]; p = 0.049). Length of hospital stay did not significantly differ among the two groups ( p = 0.65). Larger positive effect was likely to be seen for patients with a femoral neck fractures and for those without dementia. Conclusions: Patients who underwent surgery with spinal anesthesia plus FNB had better ambulatory status early after hip fracture surgery compared to patients not offered FNB. The beneficial association between FNB and ambulatory status was likely to be observed especially in patients with femoral neck fracture and without dementia.